Analyses of environmental sequences and two regions of chloroplast genomes revealed the presence of new clades of photosynthetic euglenids in marine environments - Lukešová, Soňa; Karlicki, Michał; Tomečková Hadariová, Lucia; Szabová, Jana; Karnkowska, Anna; Hampl, Vladimír (Environmental microbiology reports, 2020)
Euglenophyceae are unicellular algae with the majority of their diversity known from small freshwater reservoirs. Only two dozen species have been described to occur in marine habitats, but their abundance and diversity remain unexplored. Phylogenetic studies revealed marine prasinophyte green alga, Pyramimonas parkeae, as the closest extant relative of the euglenophytes' plastid, but similarly to euglenophytes, our knowledge about the diversity of Pyramimonadales is limited. Here we explored Euglenophyceae and Pyramimonadales phylogenetic diversity in marine environmental samples. We yielded 18S rDNA and plastid 16S rDNA sequences deposited in public repositories and reconstructed Euglenophyceae reference trees. We searched high-throughput environmental sequences from the TARA Oceans expedition and Ocean Sampling Day initiative for 18S rDNA and 16S rDNA, placed them in the phylogenetic context and estimated their relative abundances. To avoid polymerase chain reaction (PCR) bias, we also exploited metagenomic data from the TARA Oceans expedition for the presence of rRNA sequences from these groups. Finally, we targeted these protists in coastal samples by specific PCR amplification of two parts of the plastid genome uniquely shared between euglenids and Pyramimonadales. All approaches revealed previously undetected, but relatively low-abundant lineages of marine Euglenophyceae. Surprisingly, some of those lineages are branching within the freshwater or brackish genera.
Keywords: Photosynthesis; Chlorophyta; Phylogeny; DNA rostlinná; ribozomální DNA; DNA, Plant; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA, Ribosomal; RNA ribozomální 18S; Genome, Chloroplast; genom chloroplastový; Genome, Plant; genom rostlinný; Euglenida; fotosyntéza; fylogeneze; RNA, Ribosomal, 18S